2020
DOI: 10.1186/s12911-020-1068-5
|View full text |Cite
|
Sign up to set email alerts
|

Methods to improve the quality of smoking records in a primary care EMR database: exploring multiple imputation and pattern-matching algorithms

Abstract: Background: Primary care electronic medical record (EMR) data are emerging as a useful source for secondary uses, such as disease surveillance, health outcomes research, and practice improvement. These data capture clinical details about patients' health status, as well as behavioural risk factors, such as smoking. While the importance of documenting smoking status in a healthcare setting is recognized, the quality of smoking data captured in EMRs is variable. This study was designed to test methods aimed at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…In their daily practice, it is recommended that HCPs ask for and record the smoking status of their patients (Garies et al 2020 ; Van Schayck et al 2017 ; Van Zyl-Smit et al 2013 ). This may also help to monitor the impact of smoking cessation interventions (Garies et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their daily practice, it is recommended that HCPs ask for and record the smoking status of their patients (Garies et al 2020 ; Van Schayck et al 2017 ; Van Zyl-Smit et al 2013 ). This may also help to monitor the impact of smoking cessation interventions (Garies et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their daily practice, it is recommended that HCPs ask for and record the smoking status of their patients (Garies et al 2020 ; Van Schayck et al 2017 ; Van Zyl-Smit et al 2013 ). This may also help to monitor the impact of smoking cessation interventions (Garies et al 2020 ). This study found poor and inconsistent record-keeping; less than half of the HCPs always ask for and record their patients’ smoking status.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that many lifestyle factors, such as smoking, alcohol consumption, diet, and physical activity, have been implicated for increasing preterm birth risk [ 1 , 68 ]. Many of these data are recorded in unstructured fields in EHRs, and there are active efforts to develop accurate algorithms to extract these data from EHR [ 69 , 70 ]. As these approaches become robust, including lifestyle factors may further improve preterm birth prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Simpler approaches toward EHR imputation must consider whether missing values are missing completely at random (MCAR), missing at random (MAR), or missing not at random (MNAR) [ 14 ]. Conditional imputation methods may be used to account for these dependencies, most effectively if missing data are MAR [ 10 , 12 , 15 ]. While they may improve completeness and predictive precision, these methods may be computationally intensive when applied to large-scale EHR data with significant amounts of missing values.…”
Section: Introductionmentioning
confidence: 99%